On the Ludic Character of Literary Allusion - Girunyan, Gayane (Armenian Folia Anglistika, 2006)
The article investigates the possibility of viewing literary allusion as a game. More specifically, it is described as a “game-riddle” whose “deciphering”, owing to its structure and stable constituents, allows claiming that the notion of allusion is a game by nature.The article presents the scheme of understanding allusion which is based on the hermeneutic circles of part – whole, pre-understanding – understanding, cognition – knowledge. The mechanism question – answer is an ontological base not only for “deciphering” a riddle but also for interpreting an allusion, the only difference being that while a question is typical of a riddle, in case of the allusion the reader asks questions and answers them himself to arrive at understanding.